Regulation of new markets in telecommunications? Market dynamics and shrinking monopolistic bottlenecks - Charles B. Blankart; Günter Knieps; Patrick Zenhäusern (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 2006)
In the EU telecommunications regulatory framework a strong intention to avoid overregulation with respect to new markets can be observed. However, a clear-cut economically based analysis of the remaining need for sector-specific regu-lation is still missing. In this paper, the question is analyzed whether new mar-kets create new monopolistic bottlenecks or extend the borderlines of existing bottlenecks. Three kinds of transmission qualities on service markets can be dif-ferentiated according to the products provided: narrowband services like PSTN/ISDN or GSM, semi high-speed broadband services like broadband inter-net access up to 6 Mbps download and VDSL services up to 50 Mbps. As long as, due to the absence of alternative network infrastructures, a monopolistic bot-tleneck in local infrastructure networks exists the question arises what the re-maining bottleneck components are for these different markets. In this paper we will demonstrate the shrinking-bottleneck hypothesis.
More recent version: http://hdl.handle.net/10419/32309
Keywords: 330; Telekommunikationspolitik; Breitbandkommunikation; Netzzugang; Monopol; Bottleneck; EU-Staaten